Pengaruh Kinerja Keuangan Terhadap Pertumbuhan Laba pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI) Periode Tahun 2017-2020 - Harum Nuryana; Arif Hartono; Nur Sayidatul Muntiah (Universitas Muhammadiyah Ponorogo, 2022)
This study aims to determine how the influence of Banking Ratio (BR), Primary Ratio (PR) and Net Profit Margin (NPM) on the profit growth of banking companies. The population used in this study are banking companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020. Data collection uses documentation techniques obtained from the official website of the Indonesia Stock Exchange (IDX) via the www.idx.co.id link. Collecting data in this study using purposive sampling technique. The sample obtained in accordance with the specified criteria as many as 28 companies. The analytical method used is multiple linear analysis using the statistical application of SPSS Version 26. The results showed that partially the Banking Ratio (BR) and Primary Ratio (PR) variables had no effect on profit growth, Net Profit Margin (NPM) partially affected profitability. Meanwhile, the variables of Banking Ratio (BR), Primary Ratio (PR) and Net Profit Margin (NPM) have an effect on profit growth.